Quality assessment before and after knee replacement - Węgorowski, Paweł; Michalik, Joanna; Delmaczyńska, Anna; Stanisławek, Andrzej; Rząca, Macin (Journal of Education, Health and Sport, 2017)
Admission Epidemiological indicators show that the number of young people undergoing total knee arthroplasty increases. Knee implant prosthesis is a surgical procedure that involves replacing diseased cartilage and knee bones with artificial prosthesis. Research on the quality of life before and after endoscopic surgery is used to assess the effectiveness of medical activities. Purpose of research The aim of the study is to compare the assessment, quality of life of patients before the procedure of endoprosthesis and after knee arthroplasty. Materials and methods The study was conducted from February to November 2016. They covered 100 people under the care of an orthopedic clinic in the Independent Public Health Care Unit in Łęczna. Patients in the clinic were selected from 4 to 6 months after knee replacement. The method used in the work is a diagnostic survey. The research tool was a self-generated questionnaire. Discussion Implant of the knee joint replaces damaged parts of the knee. Endoprosthetic surgery is performed in patients with advanced degenerative joint disease. Studies have shown that the disease has largely affected the deterioration of patients’ physical fitness. In the studies conducted by Słowińska I. and Małdyk P. performed operations did not completely eliminate the pain. Conclusions On the basis of the research, it was concluded that the main cause of the implantation of the prosthesis was a knee injury (54%). The disease affected the deterioration of physical fitness prior to implantation of knee arthroplasty in 28% of respondents; 34% said they were very good. The quality of life after implantation of knee arthroplasty significantly improved in 57% of respondents. Self-service after surgery has improved considerably in 23% of respondents.